Strategi Pengembangan Kepribadian Positif Guru Sebagai Upaya Meningkatkan Profesionalisme Guru - Mursidin; Ahmad Rifai; Anggia Meilani Putri (Advances In Education Journal, 2026)
Teacher professionalism is one of the main factors in determining the quality of education. Apart from mastering pedagogical and professional competencies, the teacher's personality also has an important role in supporting the success of the learning process. This research aims to examine teachers' positive personality development strategies as an effort to increase the professionalism of educators. The research uses a library research method with a descriptive-analytical qualitative approach. Data was obtained from various relevant scientific literature sources, such as books, journals and academic documents related to personality development and teacher professionalism. The results of the study show that positive personality development of teachers can be carried out through strengthening behavior, attitudes, traits, characteristics, and philosophy of the teaching profession. Efforts to increase professionalism are not only the responsibility of individual teachers, but also require school support through supervision, coaching professional organizations, as well as providing supporting facilities, and government support through improving qualifications, certification, training and teacher welfare. Thus, positive personality has a close relationship with teacher professionalism because it is the foundation for building integrity, responsibility and quality of educational services.